Synthesis and Characterization of Ag(I) and Pd(II) Complexes of Some Phosphorus Ylides - Javad Sabounchei, Seyyed; Sanaie Noorani, Keyhaneh; Hejazi, Farzaneh; Samiee, Sepideh (Asian Journal of Chemistry, 2010)
Reaction of three previously reported phosphorus ylides Ph3PCHCOC6H4CH3 (Y1), Ph3PCHCOC6H4NO2 (Y2) and Ph3PCHCOC6H4Cl (Y3) with AgNO3 in 1:2 molar ratios using dichloromethane as solvent yielded mononuclear complexes of the type [(Y)2.Ag]NO3 (Y = Y1 (1), Y2 (2) and Y3 (3)). The reaction of PdCl2 with (Y2) in equimolar ratio in acetonitrile at the reflux temperature gave the complex [PdCl(μ-Cl) Ph3PCHCOC6H4NO2]2 (4) along with the phosphonium salt [Ph3PCH2COC6H4NO2]Br. The same reaction in a 1:2 molar ratio with (Y1) at the reflux temperature gave a binuclear complex of the type [PdCHP(C6H4)(Ph3)2 COC6H4CH3(μ-Cl)]2 (5) along with the phosphonium salt [Ph3PCH2COC6H4CH3]Br. This complex reacts with PPh3 in a 1:2 molar ratio in dichloromethane to give the product of bridgesplitting [PdCHP(C6H4)(Ph3)2COC6H4CH3Cl (PPh3)] (6). The characterization of these compounds was carried out by IR, 1H, 31P and 13C NMR spectroscopy and elemental analysis.